2017
DOI: 10.1080/00423114.2016.1278077
|View full text |Cite
|
Sign up to set email alerts
|

Combined emergency braking and turning of articulated heavy vehicles

Abstract: 'Slip control' braking has been shown to reduce the emergency stopping distance of an experimental heavy goods vehicle by up to 19%, compared to conventional electronic/anti-lock braking systems (EBS). However, little regard has been given to the impact of slip control braking on the vehicle's directional dynamics. This paper uses validated computer models to show that slip control could severely degrade directional performance during emergency braking. A modified slip control strategy, 'attenuated slip demand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 22 publications
2
24
0
Order By: Relevance
“…The FUKF outperformed the linear KF, producing sideslip estimate that was qualitatively similar to the RT3022 measurement, though still with significant quantitative error. Previous work [6] had revealed that when operating with lateral tyre slip only, the Fancher model could simulate the test vehicle's tyre forces on wet basalt tile surfaces with reasonable accuracy. However, significant mismatch between the model and test vehicle was found to occur under combined slip conditions.…”
Section: Observer Tuningmentioning
confidence: 99%
See 4 more Smart Citations
“…The FUKF outperformed the linear KF, producing sideslip estimate that was qualitatively similar to the RT3022 measurement, though still with significant quantitative error. Previous work [6] had revealed that when operating with lateral tyre slip only, the Fancher model could simulate the test vehicle's tyre forces on wet basalt tile surfaces with reasonable accuracy. However, significant mismatch between the model and test vehicle was found to occur under combined slip conditions.…”
Section: Observer Tuningmentioning
confidence: 99%
“…Brief descriptions of the test vehicle and experiments are provided later. Refer to [6] for further detail. Figure 9 shows a photograph of the test vehicle and a schematic of the relevant instrumentation installed.…”
Section: Application To Field Test Datamentioning
confidence: 99%
See 3 more Smart Citations